Developing Formulas for Quick Calculation of Polyhedron Volume in Spatial Geometry: Application to Vietnam - Tuan, Bui Anh; McAleer, Michael; Dang, Nguyen Thi Tieu; Pho, Kim-Hung (Journal of Reviews on Global Economics, 2019)
In the age of globalization, an effective leadership skill is the ability for quick calculation of work-related problems. From an economic perspective, fast computation often provides a competitive advantage in business, where speed, efficiency and accuracy are required. Quick calculation techniques are a central problem in modern mathematics because it shortens the time for solving technical problems. The purpose of the paper is to provide an explanation that will lead to a quick solution to a volume problem. Specifically, some convenient formulas are provided for quick calculation of the volume of the common polyhedron, together with a number of multiple-choice questions with IATA software to practice. Based on the evaluation results, reliable multiple-choice questions are used for an empirical study in Can Tho City, Vietnam on the effectiveness of the formulas for quick calculation of the polyhedron volume in spatial geometry. Statistical analysis shows that quick formulas help students to complete lessons at a higher rate, thereby contributing to improvements in the effectiveness of teaching geometry, especially the volume of the Polyhedron.